When Religion Meets Technology: Strategies of Adaptation for Students in the Digital Era - Aisyah, Inggid Aulia; Sanusi, Anwar; Mustofa, Ady Muh. Zainul (MKWK PAI Universitas Jambi, 2025)
This research aims to explore students' strategies for understanding Islam in digital media, with implementation having a positive influence if used well. Through qualitative analysis,researchers used direct interview methods with several sources to analyze how students understand Islam through the digital era. The results of this research provide knowledge about the relationship between students,religion, and the digital era, which can provide a good perspective that can develop more positive influences in this digital era. Studying Islam through technology can provide students with more understanding. Thus,these results can be a basis for the important role of students in combining Islam and the digital era.